Microwave dielectric properties and microstructure of high entropy (MgxCa0.6-xSr0.39Ba0.01)ZrO3 ceramics - Huei-Jyun Shih; Chin-Tung Shih; Ying-Chieh Lee (Open Ceramics)
The synthesis and characterization of MgxCa0.6-xSr0.39Ba0.01ZrO3 (x = 0.01, 0.03, and 0.05) ceramics using the solid-state method was investigated at varying sintering temperatures in this study. The results show that increasing MgO doping and higher sintering temperatures enhance the ceramic’s bulk density, highlighting the sintering enhancement effect of MgO. However, excessive MgO doping exceeds the solubility limit, resulting in reduced density and the formation of secondary phases. Dielectric measurements reveal that the dielectric constant increases with MgO doping up to 1 % but decreases at higher concentrations. Ceramics sintered at 1350 °C exhibit optimal dielectric properties, including a high permittivity of 32.98 and a Q × f value of 22,012 at 8–9 GHz. These results demonstrate stable dielectric performance with minimal loss at high frequency due to Mg doping as a fifth cation. This behavior suggests that dielectric relaxation is associated with the high entropy effect.